R3SOLVE: A Serious Game to Support End-of-Life Rooftop Solar Panel Waste Management - Hengky Salim (MDPI AG, 2021)
A complex systems model is necessary to holistically address the end-of-life (EoL) solar panel waste problem. However, there is a significant challenge in communicating such a model to stakeholders. Serious games can overcome this challenge by simplifying a complex model via a user-friendly interface. It enables stakeholders to experiment with different decisions and understand their long-term impacts in a safe environment. In this paper, a serious game called R3SOLVE was designed from a previously developed system dynamics (SD) model. The goal of the game is to achieve certain collection and recovery outcomes through a mix of decisions ranging from product stewardship strategies, landfill regulation, technological investment, promotional effort, reuse strategy, and infrastructure improvement. The game has a single player mode, where a player can access all decisions, and a multiplayer (turn-based) mode, where two players with different roles work collaboratively to achieve the desired outcome. Rewards and penalties also exist in the game to promote players’ extrinsic motivation to use critical thinking. Both game modes have been tested in separate workshops to identify bugs and issues regarding goal clarity and in-game information. Future directions to conduct stakeholder workshops and the evaluation approach are also suggested at the end of this paper.